Estimating water distribution of the rotating sprinkler with pulsating pressure on sloping land - Fu, Boyang; Huang, Yu; Zhang, Lin (International Journal of Agricultural and Biological Engineering, 2022)
Pulsating pressure plays an important role in improving the poor irrigation quality and the uneven water distribution caused by the terrain slope. Water distribution is one of the key factors in design of the sprinkler irrigation system, however, it is difficult to measure in practice. To provide appropriate technical parameters for the design of sprinkler irrigation system with pulsating pressure on sloping land, a mathematical model was established according to the water conservation principle and finite element idea, and its accuracy was experimentally verified. The model was applied to study the effects of terrain slope, sprinkler arrangement, sprinkler spacing and average pulsating pressure on water distribution on sloping land. The results showed that the water distribution was more favorable under the gentle terrain slope, when slope decreased from 25% to 5%, the uniformity increased from 74.47% to 86.22%. Sprinklers arranged in equilateral triangle and with the spacing close to R0 had the best water distribution uniformity, the uniformity coefficient (CU) of which was 11.43% and 8.75% higher than that in square and rectangular arrangement, respectively. The CU increased with the increase of the average pulsating pressure. However, the effect of increasing water pressure on promoting the uniformity of water distribution gradually decreases. Therefore, when using the Rainbird R5000 sprinkler on sloping land with pulsating pressure, it is suggested that the sprinkler irrigation systems should be arranged below the terrain slope of 20%, and operated at the average pulsating pressure of 300 kPa. The suitable sprinkler arrangement is the equilateral triangle, and with the spacing of 0.8R0 to 1.0R0. Keywords: sprinkler irrigation, water distribution on sloping land, estimation model, pulsating pressure DOI: 10.25165/j.ijabe.20221502.6662 Citation: Fu B Y, Huang Y, Zhang L. Estimating water distribution of the rotating sprinkler with pulsating pressure on sloping land. Int J Agric & Biol Eng, 2022; 15(2): 39–47.